Let \(\alpha\) and \(\beta\) be two roots of the quadratic equation \(x^{2}+mx-1 = 0\),where \(m\) is an odd integer.Let \(\lambda_n = \alpha^{n}+\beta^{n}\) for \(n\ge 0\).Prove that for \(n \ge 0\),

(a) \(\lambda_n\) is an integer.

(b)\(gcd( \lambda_n ,\lambda_{n+1}) = 1\)

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestWe get the relation \(\lambda_{n+1}=-m.\lambda_n+\lambda_{n-1}\).

Since \(\lambda_0=2,\lambda_1=-m\), it follows that \((\lambda_0,\lambda_1)=1\), because m is an odd integer.Also, since the first two terms are integers and we got a recurrence relation with integer coefficients, it follows that \(\lambda_n\) must be an integer.

Firstly,\((\lambda_0,\lambda_1)=1\).Let \((\lambda_n,\lambda_{n-1})=1\).Then let's assume \((\lambda_{n+1},\lambda_n)=d,d>1\).Then, using the relation we would get that \(d|\lambda_{n-1}\), which is clearly a contradiction, so we have proved it by induction.

Log in to reply

Nice ..I also solved in the same way....

Log in to reply